Thermodynamic Behavior of Ce Compounds Close to a T ->0 Critical Point - Sereni, J.G.; Schmerber, G.; Kappler, J.P.; Sereni, Julián (Institute of Electrical and Electronics Engineers, 2013)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina